Anesthesia for Patients With Burns: An Updated Review for Anesthesiologists and Nursing - Alwahbi, Khalaf Naif; Alharbi, Naif Lafi Salem; Almutairi, Fahad Mohammed; Alshammari , Muteb Alhumaidy; Alharbi , Waleed Snaid; Aldhafeeri, Mater Mazi Munahi; Alharbi, Yousef Fraih Faisl; Al Ghamdi, Fatimah Bakhit; Al Azmi, Salmah Mansour; Alfazi, Raed Muawwadh Aifan; al osaimi, Ayad theeb mubark; Al Ruwaily, Atallah Zewaiben; et al. (Journal of Ecohumanism, 2024)
Background: Burn injuries affect nearly 500,000 individuals annually, with significant implications for anesthesia management. The unique pathophysiology of burns, including airway management, hemodynamic instability, and altered metabolic responses, poses challenges for anesthesiologists. Inhalation injuries, particularly those affecting the upper airway, and systemic complications, complicate anesthesia care for burn patients. Aim: This review aims to update anesthesiologists and nursing professionals on the critical aspects of anesthetic management in burn patients, emphasizing airway management, fluid resuscitation, ventilation strategies, and addressing inhalation injuries. Methods: The article provides a comprehensive review of the pathophysiological changes that occur in burn patients, with a focus on the distinct phases of burn shock and hypermetabolic response. It discusses the anatomy, physiology, and systemic effects of burn injuries, as well as the anesthetic considerations for managing these complex cases, including airway management, ventilation strategies, and the handling of inhalation injuries. Results: The review identifies key challenges, such as airway obstruction due to supraglottic edema, the need for careful fluid management during the burn shock phase, and the importance of optimizing ventilation strategies to avoid complications like ARDS. The article emphasizes the role of fiberoptic intubation in managing difficult airways and highlights the systemic effects of inhalation injuries, such as hypoxia and acidosis. Conclusion: Effective anesthesia management for burn patients requires a thorough understanding of their unique pathophysiological conditions and careful planning. The use of appropriate anesthetic agents, careful airway management, and vigilant monitoring of systemic effects are essential in ensuring optimal outcomes. Multidisciplinary collaboration between anesthesiologists, nurses, and other healthcare professionals is critical in managing burn patients effectively